A NEW ADVANCED APPROACH FOR CONTENT BASED IMAGE RETRIEVAL USING TEXTON PATTERN - V. Lakshmi Surekha & M. Pradeep (International Journal of Research Science and Management, 2017)
In this paper, a new advanced approach for content based image retrieval using texon pattern is proposed. The proposed method collects the texton pattern which gives the structure of the query image or database image. First, the color image is converted into HSV (hue, saturation and value) color space. Second, the V color space is divided into overlapping sub blocks of size 2 × 2 and textons are collected based on the shape of the textons. Then, local binary pattern operation is performed on the texton image between the center pixel and its surrounding neighbors. Finally, the feature vector is constructed based on the contourlet transform and local binary pattern. The performance of the proposed method is evaluated by testing on benchmark database, Corel1K, Corel-5K and Corel-10K in terms of precision, recall, average retrieval precision and average retrieval rate.The results after investigation show a significant improvement as compared to the state-of-the-art features for image retrieval.